PENGARUH LINGKUNGAN KERJA DAN WORK FORM HOME TERHADAP KINERJA PEGAWAI BADAN PEMERIKSA KEUANGAN PROVINSI SUMATERA SELATAN DI MASA PANDEMI COVID-19 - Yusro Hakimah; Baidowi Abdie; Umi Hasanah (JURNAL KOMPETITIF, 2021)
This study discusses the performance of employees of the Supreme Audit Agency (BPK) Representative of the Province of South Sumatra during the Covid-19 pandemic. The purpose of this study was to determine the effect of the work environment and work form home on employee performance. The data was obtained by distributing questionnaires using google form to 54 employees using the Saturated Sampling technique. In data processing used SPSS software. The method used is qualitative analysis which is quantified and analyzed using multiple regression analysis. The results of research conducted simultaneously between all the variables studied illustrate that there is a significant positive influence of the work environment and work form home on employee performance. The results of the study prove that the work environment has a significant positive effect on work, work from home has a significant positive effect on employee performance during the Covid-19 period.